Addressing Hunger in South Africa: Food Aid and Food Security Programs for Needy Communities - Ghifari Zaka Anandi; Aswin Ariyanto Azis (Eduvest - Journal of Universal Studies, 2024)
Hunger in South Africa is a serious challenge that requires rapid and effective action to address its impacts. This research aims to explore strategies for alleviating hunger through implementing food aid programs and building food security in communities in need. The research method used is qualitative with a descriptive approach. The research results show that a combination of food aid and food security programs provides the best solution. Food aid can provide direct assistance to families in need, while food security programs aim to empower communities with the skills and resources to produce their own food. The importance of involving interested parties, including government, non-governmental organizations and the private sector, is highlighted in this research. Strong collaboration between various parties can increase the efficiency and positive impact of efforts to overcome hunger. This research makes an important contribution to understanding how best to address hunger in South Africa, providing a holistic and integrated view. It is hoped that the results of this research will serve as a guide for policy makers, humanitarian organizations and the general public in their efforts to combat hunger and improve food security in South Africa.